The Importance of Teaching the Art of Islamic Arabic Calligraphy at the University of Dar Al-Ulum Lamongan: - Hurin Innihayatus Sa'adah (Dzihni: Jurnal Pendidikan Bahasa Arab, Linguistik dan Kajian Literatur Arab, 2025)
Calligraphy is a centuries-old Islamic cultural heritage in the Arabian Peninsula. However, many people lack the skill to write Arabic calligraphy. Therefore, the Arabic Language Education Department offers calligraphy lessons to enhance the aesthetic quality of handwriting and to understand letter structures from various script styles. Consequently, the development of calligraphy education continues at the Islamic University of Darussalam Lamongan to promote this skill. This study employs a qualitative method, with students as the research subjects, who apply Islamic calligraphy directly observed during the learning process. Unstructured interviews are conducted regarding various Arabic-Islamic scripts, including: Kufic, Diwani, Thuluth, Ruq’ah, among others. Hence, the importance of studying calligraphy education emerges as part of developing the scientific, cultural, and civilizational treasury of Islam in the archipelago (Nusantara) and the wider Islamic world at the international level. Additionally, this study highlights the role of continuous practice and guidance in improving students’ competencies. Keywords: Teaching, Learning, Calligraphy Art.